Sempoating media enhances adolescent knowledge and engagement in stunting prevention - Novita Ika Wardani; Murti Ani (Poltekkes Kemenkes Yogyakarta, 2025)
Stunting remains a major public health concern in Indonesia, with the government targeting a reduction to 14% by 2024. In Blora Regency, the prevalence reached 21.5%, ranking 12th in Central Java. Adolescents, as future parents, play a critical role in the intergenerational transmission of nutritional knowledge. Sempoating media as an educational tool designed to simulate early stunting detection and prevention in toddlers aged 12–24 months was developed to enhance adolescents' knowledge and engagement in stunting prevention. This study aims to analyze the effect of Sempoating media on adolescents' knowledge and active participation in stunting prevention efforts. This quasi-experimental study used a pretest-posttest control group design conducted between June and August 2023 in Purworejo and Tutup Villages, Blora Regency, Indonesia. Sixty adolescents were recruited using total sampling and assigned to either a treatment group (received Sempoating media and module) or a control group (received only a module). Knowledge and activity scores were measured using a validated questionnaire (Cronbach’s alpha = 0.86) before and after a 3-month intervention. Data were analyzed using paired t-test and Mann–Whitney U test with SPSS version 25. There was a significant increase in knowledge and stunting prevention activities in both groups (p < 0.05). However, the treatment group showed significantly higher improvements compared to the control group, with post-intervention differences in knowledge (p = 0.026) and activities (p = 0.000). Sempoating media significantly improved adolescents' knowledge and engagement in stunting prevention. This interactive educational tool shows promise for integration into school-based and community adolescent health programs. The findings support the use of gamified media such as Sempoating as an effective strategy to empower adolescents as agents of change in reducing stunting prevalence in their communities.